ER-resident proteins are key players in cartilage and bone homeostasis - Stücker, Sina; Rellmann, Yvonne; Schulte, Sandra; Dreier, Rita (Frontiers in Cell and Developmental Biology, 2025)
Hyaline cartilage is essential for bone formation and joint function. It contains a dense extracellular matrix that is produced in the ER of chondrocytes. Therefore, the ER contains a complex machinery of enzymes including chaperones, glycosyltransferases and hydroxylases that control folding, modification and secretion of newly synthesized matrix proteins. Loss or malfunction of ER-resident chaperones and proteins leads to misfolding and accumulation of matrix proteins in the ER. This causes ER stress and disrupts crucial cellular processes including chondrocyte differentiation, signaling and matrix production. During skeletal development, deficiency of ER chaperones disrupts cartilage and bone formation by impairing the folding and maturation of collagens and other matrix proteins, causing chondrodysplasia, pseudoachondroplasia and other skeletal diseases. Loss of ER-resident chaperones also impairs the integrity and stability of the cartilage matrix, promoting its degeneration during osteoarthritis. Due to the complexity of the ER protein processing machinery, the specific roles of ER-resident proteins in cartilage and bone homeostasis largely remain elusive. This review provides an overview of the most common ER-resident proteins and our current understanding of their function in cartilage homeostasis and disease.